Pre-pregnancy BMI was associated with gestational depressive phenotypes in a population of 12,099 women in Chongqing, China - Chen, Yi; Gu, Huayan; Zhou, Niya; Zhou, Wenzheng; Cao, Jia; Chen, Qing; Zhang, Haiyan (Frontiers in Endocrinology, 2023)
Objective: To investigate the association between pre-pregnancy body mass index (BMI) and gestational depressive phenotypes. Methods: The pregnant women receiving the first prenatal examination (4th –13th week of gestation) in Chongqing Health Center for Women and Children were recruited between February 2020 and September 2021. depressive phenotypes was assessed by the Patient Health Questionnaire (PHQ-9) and the Symptom Checklist 90 (SCL-90) scale at recruitment. Pre-pregnancy weight and height were self-reported by the participants. Demographic and obstetric characteristics were obtained from the hospital information system. The association between pre-pregnancy BMI and the scores of PHQ-9 or SCL-90 scale was investigated by uni-variate analysis with Kruskal-Wallis test and by multi-variate analysis with linear regression model with adjustment of age, parity, smoking, alcohol consumption, and assisted reproduction. The association between pre-pregnancy BMI and PHQ-9 or SCL-90 diagnosed depressive phenotypes was analyzed by chi-square test and logistic regression respectively. Results: A total of 12,099 pregnant women were included, where 100% of them filled out the PHQ-9 scale and 99.6% filled out the SCL-90 scale, and 47.26% and 4.62% of the pregnant women had depressive phenotypes, respectively. Women with higher pre-pregnancy BMI had lower depressive phenotypes scores during pregnancy. Multivariate analysis of the PHQ-9 scale showed that overweight/obese subjects had a higher incidence of depressive phenotypes compared with subjects with normal BMI (OR=0.803, 95% CI [0.723, 0.892]). In a stratified analysis assessed by the PHQ-9, women who were overweight/obese prior to pregnancy were less likely to develop depressive phenotypes during pregnancy than women who were normal weight prior to pregnancy, regardless of whether they were nulliparous (OR=0.795, 95%CI[0.696,0.908]) or multiparous (OR=0.809, 95%CI[0.0.681,0.962]), while in the three age groups of 25-29 years, 30-34 years and ≥35 years, pre-pregnancy overweight/obesity were associated with lower risk of gestational depressive phenotypes. However, analysis of the SCL-90 scale showed no statistical association between depressive symptom and BMI. No substantial interaction was observed between BMI and parity or age. Conclusions: Increased pre-pregnancy BMI may be associated with reduced risk of gestational depressive phenotypes in Chinese women. Independent studies are warranted to validate the findings of the present study.